Hydrologic flushing rates drive nitrogen cycling and plant invasion in a freshwater coastal wetland model. Issue 2 (20th January 2021) - Sharp, Sean J.; Elgersma, Kenneth J.; Martina, Jason P.; Currie, William S.
Abstract: Coastal wetlands intercept significant amounts of nitrogen (N) from watersheds, especially when surrounding land cover is dominated by agriculture and urban development. Through plant uptake, soil immobilization, and denitrification, wetlands can remove excess N from flow‐through water sources and mitigate eutrophication of connected aquatic ecosystems. Excess N can also change plant community composition in wetlands, including communities threatened by invasive species. Understanding how variable hydrology and N loading impact wetland N removal and community composition can help attain desired management outcomes, including optimizing N removal and/or preventing invasion by nonnatives. By using a dynamic, process‐based ecosystem simulation model, we are able to simulate various levels of hydrology and N loading that would otherwise be difficult to manipulate. We investigate in silico the effects of hydroperiod, hydrologic residence time, N loading, and the NH 4 + : NO 3 ‐ ratio on both N removal and the invasion success of two nonnative species ( Typha × glauca or Phragmites australis ) in temperate freshwater coastal wetlands. We found that, when residence time increased, annual N removal increased up to 10‐fold while longer hydroperiods also increased N removal, but only when residence time was >10 d and N loading was >30 g N·m −2 ·yr −1 . N removal efficiency also increased with increasing residence time and hydroperiod, but was less affected by N loading. However, longer hydrologic residence time increased vulnerability of wetlands to invasion by both invasive plants at low to medium N loading rates where native communities are typically more resistant to invasion. This suggests a potential trade‐off between ecosystem services related to nitrogen removal and wetland invasibility. These results help elucidate complex interactions of community composition, N loading and hydrology on N removal, helping managers to prioritize N removal when N loading is high or controlling plant invasion in more vulnerable wetlands.